PELATIHAN PEMBUATAN SOAL KUIS MELALUI WEBSITE KAHOOT DALAM MENINGKATKAN KOMPETENSI GURU - Priyambudi, Setyo Tri; Asiah, Siti; Mulyadi, Acep; Lubis, Rabiyannur; Rohayah, Aulia Ayu (Al-Ihsan: Journal of Community Development in Islamic Studies, 2024)
In implementing the tri dharma of higher education, namely community service in sharing knowledge that has been obtained at Universitas Islam 45 Bekasi. Against the background of the problem of lack of teacher variation in using learning models in classroom learning activities. Therefore, there is a need for additions and changes in learning styles or learning methods. One of them is with training in making quiz questions by utilizing technology such as using the Kahoot website application, it is hoped that teachers can understand and understand in operating the Kahoot website as an alternative in learning variations in the classroom. The purpose of this program is that teachers can use technology as a supporting medium in learning activities and become competent in facing the world of education today has entered the era of society 5.0. The output of this program is to make a positive contribution to teachers at SDN Karangmulya 01 Karangmulya Village regarding variations in learning models using quiz question forms through the Kahoot website application which can later be applied as variations in learning methods.